2017
DOI: 10.1103/physrevlett.119.193901
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Generation of Unpolarized Light

Abstract: A Mueller tensor mathematical framework was applied for predicting and interpreting the second harmonic generation (SHG) produced with an unpolarized fundamental beam. In deep tissue imaging through SHG and multiphoton fluorescence, partial or complete depolarization of the incident light complicates polarization analysis. The proposed framework has the distinct advantage of seamlessly merging the purely polarized theory based on the Jones or Cartesian susceptibility tensors with a more general Mueller tensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…It is interesting to compare the present results with previous measurements of SHG of collagen tissue obtained with fully depolarized incident light, prepared using a microretarder array depolarizer . In that work, the NLO response was used to directly fit azimuthal and polar orientation of collagen, yielding good agreement between image analysis approaches and direct fitting to the azimuthal orientation angle of collagen.…”
Section: Results and Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It is interesting to compare the present results with previous measurements of SHG of collagen tissue obtained with fully depolarized incident light, prepared using a microretarder array depolarizer . In that work, the NLO response was used to directly fit azimuthal and polar orientation of collagen, yielding good agreement between image analysis approaches and direct fitting to the azimuthal orientation angle of collagen.…”
Section: Results and Discussionsupporting
confidence: 53%
“…Equation holds provided that the NLO process itself is intrinsically nondepolarizing, in which case the Mueller tensor M (2) allows prediction of the partially polarized state of the SHG produced by partially polarized incident light. The validity of this framework has been supported previously utilizing SHG measurements of Z -cut quartz and thin collagen sections . It was shown that for fully depolarized incident fields, resultant SHG followed intensity trends predicted by the Stokes–Mueller framework.…”
Section: Theoretical Foundationmentioning
confidence: 57%
See 1 more Smart Citation
“…Cell and western blot quantification and analysis were performed using ImageJ. Phalloidin staining (F-actin) images of single cells were analyzed for filament coherency using the OrientationJ plugin for ImageJ 59 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell quantification and analysis was performed using ImageJ ® . Phalloidin staining (F-actin) images of single cells were analysed for filament coherency using the Orientationβ plugin for ImageJ 46 .…”
Section: Methodsmentioning
confidence: 99%